An Approach to teaching autistic children - Everard, Margaret P. (Pergamon international library of science, technology, engineering, and social studies., 1976)
An Approach to Teaching Autistic Children provides guide in methods of instructing autistic children. The title does not only cover teaching methods, but also discusses behavioral management, which is a critical skill in dealing with autism.